Development of Sister City Cooperation Between Semarang and Jung-gu in 2009–2017 - Laili Nur Atikah; Damayanti, Christy; Madyar Dewi, Untari Narulita; Handayani, Tri Putri (Universitas Muhammadiyah Yogyakarta, 2023)
Located in Central Java Province, Semarang City is one of Indonesia’s major urban centers. As a type of paradiplomacy, the Regional Government of Semarang City has established sister city relationships with the governments of Brisbane (Australia), Beihai, Nanjing, and Fuzhou (China), Split (Croatia), and Jung-gu, Ulsan Metropolitan City (South Korea). At the office of the Mayor of Jung-gu in Ulsan Metropolitan City, South Korea, the Governments of Semarang and Jung-gu signed a point of cooperation formalizing their sister city relationship. Shared interests, exchanging potentials, reciprocal relationships, being actively oriented toward the community, the existence of short- and long-term strategic benefits, exclusivity and closeness in the sense of not having a sister city relationship with other cities, and stable political conditions in the country where the sister city was located were all principles that should be prioritized in carrying out this cooperation. The historical foundations of the diplomatic relationships between Semarang and Jung-gu were bolstered by infrastructure and natural resources facilitating and encouraging further development of the two cities’ previously substantial relations.